Sustainable fertilizer management for reduction of greenhouse gases emission in bamboo forest - Jiang Jianhui; Zhang Jianying; Hu Hong (浙江大学学报. 农业与生命科学版)
Excessive fertilizer use has been recognized as a key factor in increasing agricultural and forestry greenhouse gases (GHG) emission. Previous studies found that proper fertilizer using control strategy can reduce agricultural CO2, N2O, CH4 emission, however, influence crop yields as well. Bamboo is an important economic plant in China, which has been intensively cultivated in recent years to satisfy increasing social demands of bamboo products. To maintain rapid growth of bamboo, the fertilizer using amount in bamboo forest is significantly higher than other human-planted forests such as Pinus massoniana and eucalyptus forest. Therefore, it is necessary to explore a sustainable fertilizer management approach which could achieve the optimum balance between low GHG emission and high production in bamboo forest.The purpose of this study is to develop a sustainable fertilizer management approach by estimating the impact of different fertilization practices on GHG emission and biomass production of bamboo forest comprehensively. It is supposed to reduce current GHG emission from bamboo plantation without inhibiting bamboo production.Integrated with the surveys/statistics data, the DNDC (denitrification-decomposition) biogeochemical model was applied to simulate seven typical fertilization scenarios of a Moso bamboo forest in Anji County, Zhejiang Province during 2000—2010. The fertilization scenarios were designed by different fertilizer types (commercial organic compound fertilizer, cow manure, ammonium bicarbonate) and application dosages (medium, low, high). Three indicators were adopted for the assessment: 1) the global warming potential (GWP) to assess the total CO2 and N2O emission from studied bamboo plantation;2) the net primary production (NPP) to assess the bamboo production;3) the GHG emission per bamboo biomass increments (Cflux/Cbiomass). All the indicator values were calculated from the DNDC modeling results.According to the assessment results, manure had the strongest effect on reducing GHG emission by increasing the soil organic carbon (SOC), and the GWP under high amount of commercial organic fertilizer and manure application (scenario MH) decreased to -11.3 t/(hm2·a) while the value under none fertilization condition was 1.7 t/(hm2·a); the inorganic N fertilizer showed no obvious impact on CO2 emission but had strong effect on stimulating N2O emissions, and the high amount of inorganic N fertilizer (scenario ABH) led to a 12.2 times higher net GWP than the situation without fertilization, which was recognized as the most negative scenario for low-carbon fertilizer management. Under seven fertilization scenarios, the bamboo biomass increments showed no obvious difference compared with the situation without fertilization. However, the NPP under the M scenario (common amount of commercial organic fertilizer and manure) was slightly higher than other scenarios with the value of 4.71 t/(hm2·a), indicating that organic fertilizers and manure have stronger effect on improving bamboo production. Without inhibiting bamboo production, the high amount of manure application resulted in the lowest net GWP for per net primary production increment (-2.4 kg/kg), which had the most significant GHG reduction among all other scenarios.As a consequence, organic fertilizer shows more potential on reducing CO2, N2O emission without decreasing bamboo production. From the GHG emission reduction perspective in sustainable fertilizer management for bamboo forest, advocating organic fertilizer application and reducing inorganic N fertilizer use can be a plausible approach towards the dual objectives of high bamboo production and GHG emission reduction.